Statistical Analysis of Selected Heavy Metals in Indoor and Outdoor Dust in the Area around Kota Thermal Power Plant, Kota, Rajasthan (Journal of Scientific Research, 2025)
This study was carried out to investigate the concentration of six heavy metals (Cu, Pb, Cd, Zn, Ca and Fe) under meteorological influence in indoor and outdoor dust samples collected during the winter months namely November 2022 to February 2023 in the vicinity of Kota, Rajasthan. The average values of Cu, Pb, Cd, Zn, Ca and Fe concentrations (mg/L) are found to be 1.0432, 3.8961, 0.6017, 5.9503, 2205.08 and 77.0935 in indoor and 0.8281, 3.5099, 0.5665, 6.0942, 2622.74 and 80.8036 in outdoor dust samples, respectively. The concentration of studied metals is influenced by the prevalent meteorological environment during the study period although alterations are observed in this trend possibly due to varying wind speed. Wind roses indicate that the sampling sites confronting primarily North wind blow (26.97%) from the point source Kota Thermal Power Plant (KTPP) are found to have the highest metal burden due to their location being closest to the source. Pearson’s correlation, Enrichment factor and Principal component analysis indicate that the Cu, Pb, Cd and Zn are mainly originated from coal burning activities at KTPP besides other industrial activities in the study area.